Clathrin light chains are required for the gyrating-clathrin recycling pathway and thereby promote cell migration - Majeed, Sophia R. (Nature Pub. Group, 2014)
The clathrin light chain (CLC) subunits participate in several membrane traffic pathways involving both clathrin and actin, through binding the actin-organizing huntingtin-interacting proteins (Hip). However, CLCs are dispensable for clathrin-mediated endocytosis of many cargoes. Here we observe that CLC depletion affects cell migration through Hip binding and reduces surface expression of β1-integrin by interference with recycling following normal endocytosis of inactive β1-integrin. CLC depletion and expression of a modified CLC also inhibit the appearance of gyrating (G)-clathrin structures, known mediators of rapid recycling of transferrin receptor from endosomes. Expression of the modified CLC reduces β1-integrin and transferrin receptor recycling, as well as cell migration, implicating G-clathrin in these processes. Supporting a physiological role for CLC in migration, the CLCb isoform of CLC is upregulated in migratory human trophoblast cells during uterine invasion. Together, these studies establish CLCs as mediating clathrin–actin interactions needed for recycling by G-clathrin during migration.